Monitoring of Aedes aegypti Linneaus (Diptera: Culicidae) in the urban radius of the city of Diamante - Campos Soldini, Maria Paula (2019)
Vector transmitted diseases are a priority problem and have become relevant in places where they were not previously important. In recent years, our country has seen an increase in the number of Dengue cases. For the efficient control of this disease, it is essential to monitor the vector by means of sensitive methods that favor early and sure detection with precise, rapid decision making that gives rise to efficient control strategies. The objective of this study was to follow the population of A. aegypti in the town of Diamante (Entre Ríos) and also to study the oviposition behavior of the female. For this, 11 campaigns were carried out between the months of February and April 2015 in a total of 32 sites per sampling; a total of 352 samples collected. The IDO and IPO (indices) were applied and analyzed; as well as analysis of variance (ANOVA) and simple linear regression. The relative humidity, temperature and rainfall data were obtained from the meteorological station of CICYTTPCONICET. We observed that the oviposition of the female A. aegypti and therefore its spatial distribution is similar in the urban center as in the city’s peripheral surroundings. Even so, the spatial distribution of the infestation occurs in the city center area. The strict dependent variable for the oviposition of the female is the rise in temperature. Also, an effective reduction of the reservoirs was obtained, since this information was transmitted to official agencies to coordinate and implement control strategies destined at reducing the population of the insect vector.